Dynamics and control issues for fault tolerance - Patrick S. Keogh (2018)
This chapter will consider some key issues in the fault tolerant design of magnetic bearing systems. The chapter deals primarily with control considerations, while more general aspects are covered in Chap. 18 on Safety and Reliability Aspects. The first section surveys typical faults that may need to be accommodated and provides some suggestions for mitigation. The second section considers the dynamics of an AMB controlled rotor during touch-down bearing interaction. © 2009 Springer-Verlag Berlin Heidelberg.